Subprime Crisis and Financial Accounting Issues Raise in This Crisis - Zhou, Peng (2009)
Subprime crisis brought to us a global financial disaster. The whole world has yet recover from this disaster, however, it is important to understand the cause of this disaster and seeking the core factors that caused this crisis, determinate financial accounting issues being ignored and covered underneath the bubbled boost market. And this could be significant to warm the world and prevent this crisis from happening in future again. In this paper, I will try to answer those questions base on data and scholars and analyze by adopting quantitative and qualitative researches.